Development of Histology Teaching Materials of Five Human Organs Magazine Based on Corel Draw for Student at IKIP Budi Utomo Malang - Septina Dwi Prasetyana; Eka Corneliawati (BIOEDUKASI, 2018)
The purpose of this study was to develop a new learning media in the form of a magazine to support the histology learning process. The presence of the Five Human Organs Magazine is expected to provide a new learning atmosphere during the learning process, and to be able to provide new information on the topic of histology of the five organs of the human body, namely the brain, lungs, stomach, heart and liver. The development model used in this study was 4D development model from Thiagarajan (1974). The 4D model has 4 stages, namely define, design, develop, and disseminate. But in this study it was only carried out until the develop stage without disseminate stages. The sample used in the trial was a class A of 2016 consist of 40 students. Data obtained by means of questionnaires. The results showed that the development of teaching materials for five human organs magazines was suitable to use in learning activities. This was indicated by the result expert validation which revealed that the product was very good. Validation result for learning media and learning design were said to be very good. Individual and group trial data said that the product was very good. In the medium group trial it can be concluded that the teaching material of the five human organs magazine is suitable to be used as a reference for the histology teaching material by students in IKIP Budi Utomo Malang. Keywords: Histology teaching materials, magazine, five human organs.